2014
DOI: 10.1017/s1041610214001380
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and cognitive outcomes in a nationally representative sample: the National Health and Aging Trends Study

Abstract: Background The prevalence of both type II diabetes mellitus (DM) and cognitive impairment is high and increasing in older adults. We examined the extent to which DM diagnosis was associated with poorer cognitive performance and dementia diagnosis in a population-based cohort of US older adults. Methods We studied 7,606 participants in the National Health and Aging Trends Study, a nationally representative cohort of Medicare beneficiaries aged 65 years and older. DM and dementia diagnosis were based on self-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 28 publications
0
17
0
1
Order By: Relevance
“…There are multiple mechanisms that may explain the associations observed between napping and cognitive function. Napping is associated with greater risk for several medical conditions including type‐II diabetes, incident cardiovascular disease, and greater odds of obesity, which are themselves associated with cognitive deficits . However, we adjusted for medical morbidity and still found an association between napping and cognition.…”
Section: Discussionmentioning
confidence: 78%
“…There are multiple mechanisms that may explain the associations observed between napping and cognitive function. Napping is associated with greater risk for several medical conditions including type‐II diabetes, incident cardiovascular disease, and greater odds of obesity, which are themselves associated with cognitive deficits . However, we adjusted for medical morbidity and still found an association between napping and cognition.…”
Section: Discussionmentioning
confidence: 78%
“…Here, we investigated the association between DM and cognitive test performance and dementia over a five-year period in a large, nationally representative sample of adults 65 years old and older – the National Health and Aging Trends Study (NHATS). Our previous work in NHATS showed that DM was cross-sectionally associated with poorer performance on cognitive tests, but not dementia diagnosis (Wennberg et al, 2014). In this longitudinal study we hypothesized that DM would predict incident dementia diagnosis and decline in cognitive performance over time, above and beyond what might be expected with age.…”
Section: Introductionmentioning
confidence: 99%
“…However, Wennberg et al 21 reported a similar frequency of this self-rated disease (24%) in a representative sample of American seniors (≥65 years).…”
Section: Discussionmentioning
confidence: 85%